Extended Spectrum Beta-Lactamase Carriage State among Elderly Nursing Home Residents in Beirut - M. A. Jallad; R. Naoufal; J. Irani; E. Azar (The Scientific World Journal)
Introduction. ESBL-producing Enterobacteriaceae can cause severe infections, but they are also isolated from the stool of asymptomatic subjects. Faecal carriage of such organism is poorly understood. Methods. First phase of the study was cross-sectional with prevalence and epidemiology of ESBL faecal carriage in two nursing homes in Beirut: 57 residents in the first (NH1) and 151 residents in the second (NH2). In second phase, faecal swabs from cohort of NH1 residents were examined for carriage at six-week intervals over three-month period. Residents’ charts were reviewed to assess carriage risk factors. Results. Over 3 consecutive samplings at NH1, 81% of residents were at least one-time carriers with 50% at the first round, 60.4% at the second, and 74.5% at the last one. At NH2, 68.2% of residents were carriers. Constipation (in NH1) and antibiotic intake (in NH2) were significantly associated with higher ESBL faecal carriage while the length of stay at the nursing home (in NH2) was associated with less carriage. Conclusion. Faecal carriage of ESBL-producing Enterobacteriaceae is high among nursing home patients in Beirut. The rate of carriage changes rapidly and significantly over time either with multiple factors playing a possible role like outbreak spreading, antibiotic, and health care system exposure.